Aplikasi Elektronik Data Processing of Making Land Certificates Pada Kantor Pertanahan Kota Payakumbuh - Wifra Nazri; Wifra Safitri; Dhio Saputra (Universitas Pahlawan Tuanku Tambusai, 2020)
Basically, The Development which of technology influences human activities. Computer is one advantages of technology development which can support quality and quantity of works. By using the computer as one tool in the presentation of information data Especially processing of transaction data on Kantor Pertanahan Kota Payakumbuh supported by MySQL applications can support the speed of data processing as efficiently as possible. Based on Direct survey which and been done in statistic Institution Centre by using Technical interview and learning some related references or literatures. This now system would be implemented and could amount quality of information in order to be useful to the institution.